Предмет: Математика,
автор: vika676564
представить в виде многочлена:а(а+1)*(а-1)
Ответы
Автор ответа:
0
(a^2+a)*(a-1)=a^3-a^2+a^2-a
Сокращаем -a^2 и +а^2 . получаем a^3-a
Сокращаем -a^2 и +а^2 . получаем a^3-a
Автор ответа:
0
а(а+1)*(а-1)=а(а2-а+а-1)=а(а2-1)=а3-а
а2- а в квадрате
а3- а в кубе
Ответ: а3 - а
а2- а в квадрате
а3- а в кубе
Ответ: а3 - а
Похожие вопросы
Предмет: История,
автор: bakausodayo2
Предмет: Английский язык,
автор: Аноним
Предмет: Геометрия,
автор: Аноним
Предмет: Алгебра,
автор: 20010802а